2020
DOI: 10.1101/2020.01.23.20018507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The cholinergic system and treatment response in subtypes of Alzheimer’s disease

Abstract: BACKGROUND: The heterogeneity within Alzheimer's disease (AD) seriously challenges the development of disease modifying treatments. We investigated volume of the basal forebrain, hippocampus, and precuneus in atrophy subtypes of AD, and explored the relevance of subtype stratification in a clinical trial on encapsulated cell biodelivery (ECB) of nerve growth factor (NGF) to the basal forebrain. METHODS: Structural MRI data was collected for 90 amyloid-positive patients and 69 amyloid-negative healthy controls … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…22,23 MRI studies have also consistently identified a fourth subtype displaying minimal brain atrophy. [16][17][18][19][20][21][23][24][25][26] In contrast, data-driven methods do not depend on a priori selection of brain regions but investigate interindividual variation in measures of volume or cortical thickness. Several algorithms have been used.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…22,23 MRI studies have also consistently identified a fourth subtype displaying minimal brain atrophy. [16][17][18][19][20][21][23][24][25][26] In contrast, data-driven methods do not depend on a priori selection of brain regions but investigate interindividual variation in measures of volume or cortical thickness. Several algorithms have been used.…”
Section: Resultsmentioning
confidence: 93%
“…12 Hence, neurodegeneration measures are another plausible vein to defining biological subtypes. Several hypothesis-driven MRI studies have reported data on these subtypes by using visual rating scales of brain atrophy [16][17][18][19][20][21] or automated methods for estimating regional brain volume. 22,23 MRI studies have also consistently identified a fourth subtype displaying minimal brain atrophy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Risacher et al (2017) also corrected for age, sex and ICV, but they based this correction on a reference group of amyloid-beta negative (Aβ−) healthy controls and used a different correction method additionally including the MRI field strength. Ferreira et al and follow-up studies from our lab used visual rating scales of brain atrophy in medial temporal, frontal and posterior cortices ( Ferreira et al , 2017 , 2018 , 2019 ; Persson et al , 2017 ; Ekman et al , 2018 ; Oppedal et al , 2019 ; Machado et al , 2020 ) and determined clinical cut points for abnormality ( Ferreira et al , 2015 ). We also used unsupervised clustering in another cross-sectional study by Poulakis et al (2018) , which was recently extended for subtyping on longitudinal data ( Poulakis et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Risacher et al (6) also corrected for age, sex, and ICV, but they based this correction on the amyloid-beta negative (Aβ-) healthy controls as the reference group, and used a different correction method that also included the MRI field strength. Studies from our lab used visual rating scales of brain atrophy in medial temporal, frontal, and posterior cortices (7)(8)(9)(10)(11)(12)(13), and determined abnormality based on clinical cut points (14). We also used an unsupervised clustering method in another cross-sectional study (15), which has recently been extended for subtyping on longitudinal data (16).…”
Section: Introductionmentioning
confidence: 99%